Modelling consumers’ sustainability consciousness impact on sustainable purchase intention - Carvalho, Bárbara Leão de (2015)
This thesis examines the triggers towards consumers’ sustainable consumption, which allows a deeper understanding on an integrated “Triple Bottom Line” perspective the drivers towards the conscious consumption of sustainable products. Thus, the Consumers’ Sustainable Consciousness Model is proposed as an alternative to study Sustainability with an integrated approach. The four proposed constructs of the model were defined using the C-OAR-SE methodology and measured and validated using both exploratory and confirmatory factor analysis with a battery of 46 items and two independent samples. Also in this research the theoretical framework is measured using SEM (Structural Equation Modelling) in order to test the relation between constructs and confirm the eleven research hypotheses. It was found that is more important to launch the aligned portfolio with the desired products than to develop a sustainably sound brand. The findings also showed that multiple constructs and dimensions lie behind sustainable consumer purchase intention but that overall it is more important to launch a portfolio with the desired sustainable products attributes than to develop a sustainably sound brand. The findings also revealed that it is more relevant to consumers to perceive brand attitudes as righteous than as opportunistic, but this fact doesn’t change much consumers purchase intention, even though there is appears to be more relevant to purchase sustainably through trust rather than through accessibility. On contrary, if consumers perceive that products have sound sustainable attributes, this appears to as a much more relevant factor to purchase sustainably specially through trust rather than through accessibility. Finally, theoretical and practical implications of the study are also discussed.